Management of CML-blast crisis - Hehlmann, Rüdiger; Saußele, Susanne; Voskanyan, Astghik (Best practice & research, 2016)
Tyrosine kinase inhibitors (TKI) have moderately improved survival in BC, but a median survival of less than 1 year is still unsatisfactory. This article reviews the various tests required for diagnosis of BC, features at diagnosis, treatment modalities (intensive chemotherapy, TKI, allo-SCT and a selection of investigational agents), options of prevention and predictors of progression. The best prognosis is observed in patients that achieve a 2nd CP. Allo-SCT probably further improves prognosis of patients in 2nd CP. The choice of TKI should be directed by the mutation profile of the patient. BC can be prevented. A careful analysis of risk factors for progression may help. Current treatment options are combined in a concluding strategy for the management of BC.